SPIRITUALITY AS AN EXISTENTIAL DIMENSION: EMPHASIZING THE HISTORICAL AND SOCIAL INFLUENCES OF CHRISTIANITY (CIPEEX, 2025)
This study explores the role of spirituality in human development, focusing on its moral, social, and psychological influences within the contemporary Western context, particularly through the lens of Christianity. Spirituality, though often marginalized, is examined as a critical factor in shaping ethical values, social relationships, and mental and physical well-being. The research employs a mixed-method approach, combining bibliographic analysis of works by authors such as Vishal Mangalwadi, C.S. Lewis, and Max Weber, and empirical data collected through focus groups with Christian bishops. The results highlight Christianity’s historical and social impact, including its contributions to human rights, social justice, education, and scientific thought. The findings underscore spirituality as an essential dimension for integral human development, promoting ethical guidance, emotional resilience, and a sense of purpose. This study advocates for inclusive and informed discussions on spirituality in academic and practical contexts.